2020
DOI: 10.1002/jssc.201901121
|View full text |Cite
|
Sign up to set email alerts
|

Targeted and nontargeted screening and identification of 50 antihypertensive adulterants in dietary supplements and herbal medicines using quadrupole–orbitrap high resolution mass spectrometry with compound database

Abstract: In the present work, a novel database of drug compounds and a rapid screening method based on ultra‐high performance liquid chromatography coupled to high resolution orbitrap mass spectrometry were developed and applied in the screening and identification of targeted and nontargeted antihypertensive adulterants in dietary supplements and herbal medicines. The established screening database includes retention time, exact mass, fragments, isotopic pattern, and MS2 spectra library of the target compounds and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Overall validation results were summarized in Tables 1 and 2. In this study, calculated LODs for 92 targeted compounds were comparable with previously reported analytical methods using UHPLC-high resolution MS [41][42][43]. The previously reported methods provided LOD ranges within 0.3-2 ng/g, 0.01-0.04 µg/g, and 0.12-1.50 µg/mL, for 13 weight-loss drugs, 50 antihypertensive adulterants, and 20 antigout and anti-osteoporosis drugs, respectively.…”
Section: Methods Applicationssupporting
confidence: 84%
See 1 more Smart Citation
“…Overall validation results were summarized in Tables 1 and 2. In this study, calculated LODs for 92 targeted compounds were comparable with previously reported analytical methods using UHPLC-high resolution MS [41][42][43]. The previously reported methods provided LOD ranges within 0.3-2 ng/g, 0.01-0.04 µg/g, and 0.12-1.50 µg/mL, for 13 weight-loss drugs, 50 antihypertensive adulterants, and 20 antigout and anti-osteoporosis drugs, respectively.…”
Section: Methods Applicationssupporting
confidence: 84%
“…Under the optimized conditions, LODs ranged from 0.1 to 16 ng/g. Furthermore, most substances adulterated in illegal drugs and supplements were found at mg/g levels [41][42][43][44]. Considering the concentration levels of detected adulterants in previous studies, this method enabled sensitive detection for screening of 92 illegal adulterants.…”
Section: Methods Applicationsmentioning
confidence: 89%
“…The combination of targeted and untargeted identification strategies has been successfully applied to the identifi-cation and characterization of TCM components many times. Hence, similar strategies have been employed in the present study [19][20][21]. Compounds contained in SHL preparations were searched in Chemspider, PubMed, Elsevier Science Direct, and Massbank databases.…”
Section: Identification Of the Chemical Constituents In Shl Dosage Formsmentioning
confidence: 99%
“…Ultra-high/high-performance liquid chromatography technique (UH/HPLC), combined with highresolution quadrupole/time-of-flight mass spectrometry (Q-TOF/MS) or triple quadrupole mass spectrometry (QQQ/MS), has been not only used as an effective and powerful technique for qualitative analysis of almost all of the components, but also internationally acknowledged for the quality evaluation of TCM, TCM formula, or their related products [13,14]. The former technique is an efficient tool for high-throughput screening of compounds due to the 2D acquisitions modes, including data-independent acquisition (MS E ) and fast data-directed analysis (Fast DDA).…”
Section: Introductionmentioning
confidence: 99%